Flipped Classroom Assisted Canva to Improve the Reports Writing Skills of Vocational School Student - Leny Ocktalia; Sujinah; Saada Omar (The Indonesian Institute of Science and Technology Research, 2023)
This classroom action research was intended to improve the students’ writing report ability in the 11th grade students of vocational school. The method used was the flipped classroom method assisted by Canva media. The research design was classroom action research which was implemented in two cycles. The subjects of the research were the 11th grade students with the total number of the students were 31 students. The research data was collected by using observation and testing methods which were analyzed by using quantitative descriptive techniques. The results showed that there was an improvement in the percentage of professional placement report writing ability from 32.2% in the pre-cycle to 64.5% in the first cycle. There was significant improvement in the percentage of professional placement report writing ability from 64.5 % in the first cycle to 81% in the second cycle. The application of the flipped classroom method assisted by Canva media in Indonesian subjects has improved the ability in writing professional placement report of the 11th grade students.